2007
DOI: 10.1259/bjr/42250860
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous renal masses following intravesical bacillus Calmette–Guérin therapy: the central unaffected calyx sign

Abstract: A 67-year-old man with a history of melanoma, treated surgically 7 years before, was referred for vomiting and right flank pain after three intravesical instillations of bacillus Calmette-Guérin (BCG) for superficial bladder cancer. A CT scan showed a mass on the right kidney, with a normal calyx in its centre. Percutaneous biopsy, obtained because of melanoma history, showed granulomatous reaction caused by BCG infection. The renal mass disappeared after 9 months of anti-tuberculous treatment. The presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12]16,20 Perhaps the absence of fever in the two cases presented here could be related to the dose and strain of BCG used. Whereas in these two cases, 50 mg of BCG Tice strain was used, previous reports of febrile renal granulomas were reported with BCG Connaught strain 5,11,16 or BCG Tice strain at higher dose of 120 mg per installation. 9 A recent randomized clinical trial has shown that superior immunogenicity and efficacy of BCG Connaught strain when compared with BCG Tice strain.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…[3][4][5][6][7][8][9][10][11][12]16,20 Perhaps the absence of fever in the two cases presented here could be related to the dose and strain of BCG used. Whereas in these two cases, 50 mg of BCG Tice strain was used, previous reports of febrile renal granulomas were reported with BCG Connaught strain 5,11,16 or BCG Tice strain at higher dose of 120 mg per installation. 9 A recent randomized clinical trial has shown that superior immunogenicity and efficacy of BCG Connaught strain when compared with BCG Tice strain.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, several cases of nephroureterectomy have been reported since these masses were mistaken for renal cell carcinoma or urothelial carcinoma. 10,12,16 When analyzing available published case reports on renal granulomas, we found that most cases reported multifocality of renal granulomas with multiple renal masses on imaging studies, 4,8,[11][12]16 while others reported solitary renal foci. 5,7,9,10 Both patients in the present series had multiple renal granulomas.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations